MODEL PENILAIAN KINERJA (PERFORMANCE APPRAISAL) KEPALA SEKOLAH MENENGAH PERTAMA NEGERI - Kurniady, Dedy Achmad; -, Sururi; -, Suryadi (PEDAGOGIA, 2016)
The role of the principal is important for directing school life to achieve school goals. The principal appointment is attained through formal and rational consideration, determined by procedures, requirements, and regulations. This study is concerned with the development of performance appraisal model of junior high school principals and is aimed to achieve the following aims: 1) to detect rules and system regarding principals performance appraisal; 2) to verify and describe components, process and measures results of principals appraisal, and 3) to analyse Performance Based required by principals; and 4) to generate hypothetical models of principal performance appraisals in junior high school level. In order to have principals with all standard criteria, efforts to improve principal professional capacities are needed to conduct in a well-planned manner through continuous quality improvement. These improvements are mapped out intermittently so that principals profiles based on measures results of Principals Performance Appraisal can be put into actual. Performance appraisal is designed to identify data on principals performance.